The simplified form of27–√+5–√+712−−√−5–√+512−−√−7–√is = ?The simplified form of27+5+712−5+512−7is = ?\eqalign{ & {\text{The simplified form of}} \cr & \frac{2}{{\sqrt 7 + \sqrt 5 }} + \frac{7}{{\sqrt {12} - \sqrt 5 }} + \frac{5}{{\sqrt {12} - \sqrt 7 }}{\text{is = ?}} \cr} " /> The simplified form of27–√+5–√+712−−√−5–√+512−−√−7–√is = ?The simplified form of27+5+712−5+512−7is = ?\eqalign{ & {\text{The simplified form of}} \cr & \frac{2}{{\sqrt 7 + \sqrt 5 }} + \frac{7}{{\sqrt {12} - \sqrt 5 }} + \frac{5}{{\sqrt {12} - \sqrt 7 }}{\text{is = ?}} \cr} " /> The simplified form of27–√+5–√+712−−√−5–√+512−−√−7–√is = ?The simplified form of27+5+712−5+512−7is = ?\eqalign{ & {\text{The simplified form of}} \cr & \frac{2}{{\sqrt 7 + \sqrt 5 }} + \frac{7}{{\sqrt {12} - \sqrt 5 }} + \frac{5}{{\sqrt {12} - \sqrt 7 }}{\text{is = ?}} \cr} " />
Post your Comments